بلتستانی شعرا پر اقبال کے اثرات کا توضیحی مطالعہ: An explanatory study of Iqbal’s influence on Balti poets - Mazhar Ali Abbas (Tashkeel e Jadeed, 2025)
Allama Iqbal was one of those poets who gave people a dream, a new aspiration. Allama Iqbal was that brilliant poet of the Indian subcontinent who changed the course of time with his poetry. Iqbal's poetry is universal, and its effects have reached the land of Baltistan. Poets of Baltistan have also benefited from Iqbal's thought consciously and unconsciously. In the present era, where a lot of research is being done on Iqbal Studies, it is important to see how the poets of Baltistan adopted Iqbal's thought and to what extent they were able to access Iqbal's real thought. This article examines the intellectual impact of Iqbal on these Baltistan poets.